PEMBUATAN KERAJINAN MELALUI PEMANFAATAN SAMPAH PLASTIK DI DUSUN NGANDAT DESA MOJOREJO - Novi Puji Lestari; Rizki Febriani (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2019)
Mojorejo Village is one of the villages located in the Batu City Government area of ​​Malang Regency. The village, which is located close to the center of Batu City, has many positive benefits related to waste management, namely the presence of several home industries and a Buddhist campus in this area that generates income and has a negative impact, which is related to waste . The intended waste is plastic waste which so far with the village PKK has been sorted between plastic and non-plastic waste but there has been no special treatment for the sorting apart from being sold only to collectors of flea or junk goods. In addition, there are also a number of spots in the mandatory hamlet which are slums and a lot of plastic waste. Starting from this problem, the dedication team from the University of Muhammadiyah Malang will help provide training to local residents who have a lot of plastic waste to make products that are worth selling. The dedication team also provided assistance in the form of a special plastic sewing machine to facilitate the manufacture of handicraft products.